Β-Maleimide substituted meso-arylporphyrins: Synthesis, transformations, physico-chemical and antitumor properties. (December 2019) - Ol'shevskaya, Valentina A.; Alpatova, Viktoriya M.; Radchenko, Alexandra S.; Ramonova, Alla A.; Petrova, Albina S.; Tatarskiy, Victor V.; Zaitsev, Andrei V.; Kononova, Elena G.; Ikonnikov, Nikolay S.; Kostyukov, Alexey A.; Egorov, Anton E.; Moisenovich, Mikhail M.; et al.
Abstract: The maleimide moiety is widely used in drug design. To explore the properties of maleimide containing photosensitizers we obtained a series of new β -maleimide functionalized meso -arylporphyrins through acylation of β -amino group in porphyrins with maleic anhydride followed by condensation of maleic acid monoamides. The selective reactivity of porphyrin maleimides toward thiols was demonstrated using mercaptocarboranes and cysteine. New derivatives retained the ability of tetrapyrrolic macrocyclic compounds to absorb light in visible spectral region and to generate triplet states and reactive oxygen species upon photoactivation. Importantly, illumination of cells loaded with a cell permeable 2-{3-[( o -carboran-1′-yl)thio]pyrrolidine-2, 5-dione-1-yl}-5, 10, 15, 20-tetraphenylporphyrin triggered rapid (within the initial minutes) generation of superoxide anion radical concomitantly with a decrease of mitochondrial membrane potential, and then the loss of the plasma membrane integrity and cell death. Thus, the maleimide-substituted porphyrins represent a new chemotype of polyfunctionalized compounds for an in-depth investigation as photosensitizers in cancer and beyond. Graphical abstract: Image 1 Highlights: A panel of new β -maleimide-substituted meso -arylporphyrins was synthesized. Reactivity of porphyrin maleimides towards S-nucleophiles was studied. Flash photolysis showed the ability of new compounds to generate ROS. Complexes with albumin were determined for maleimide and succinimide porphyrins. Selected compounds induced rapid photonecrosis in colon carcinoma cells.